Certain Indefinite Integrals Involving Harmonic Number (Global Journal of Science Frontier Research, 2014)
In this paper we have established certain indefinite integrals involving Harmonic Number. The results represent here are assume to be new.
Keywords: pochhammer symbol; gaussian hypergeometric function; harmonic number